Efficacy of Nursing Action Documentations in the Clinical Settings - E. N., Chiejina (International Journal For Research In Health Sciences And Nursing, 2019)
Nursing documentation is a vital component for safe, ethical and effective nursing care. This study investigated the efficacy of Nursing action documentations in the clinical settings. Documented nursing actions for 264 clients were obtained from two Tertiary, two Secondary and two Primary health care institutions in Anambra State of Nigeria using judgmental and simple random sampling techniques. One research question and three null hypotheses guided the study. The instrument used for data collection was checklist on Nursing Documentation in the Clinical Setting. Standard descriptive statistics of frequency, means and standard deviation were used to summarize the variables. Pearson Product moment correlation and Analysis of Variance were adopted to answer the research question and in testing the hypotheses at 0.01 and 0.05 levels of significance respectively. The result indicated significant relationship between the core principles of nursing documentation and the timeliness of the documentation, significant relationship between preciseness of nursing documentation and the legal implications, as well as significant differences in nursing documentations across the three levels of healthcare institutions.